Personalized 3D-Printed Gastroretentive Drug Forms with Metronidazole - Révész, Réka; Mengenli, Akay Dogan; Béres, Mónika; Arany, Petra; Haimhoffer, Ádám (De Remediis, 2025)
3D printing is increasingly recognized as a versatile manufacturing approach, enabling the production of devices that are difficult or costly to fabricate using conventional methods. In this study, we aimed to develop a hollow, 3D-printed capsule designed for incorporation of a molten matrix containing an active pharmaceutical ingredient, and to evaluate its potential for gastric retention through controlled drug release. Capsule shells were fabricated from polylactic acid using fused deposition modeling and subsequently filled with polyethylene glycol-based melts. Micro-CT was employed to assess internal structure and integrity. Drug release profiles were measured for different matrix compositions, and texture as well as compositional analyses were performed on both filled and unfilled capsules. Our findings demonstrate that the 3D-printed PLA shells provide sufficient mechanical strength and, depending on the matrix composition, enable controlled, zero-order drug release for up to five hours. These results highlight the potential of 3D-printed capsules as a customizable, gastro-retentive drug delivery system, offering opportunities for personalized therapies.